Suppression of structural instability in LaOBiS2−xSex by Se substitution. (22nd October 2018) - Paris, E; Mizuguchi, Y; Wakita, T; Terashima, K; Yokoya, T; Mizokawa, T; Saini, N L
Abstract: Isovalent substitution of S by Se in LaOBiS2− x Se x has a substantial effect on its electronic structure and thermoelectric properties. To investigate the possible role of BiS2 structural instability, we have studied the local structure of LaOBiS2− x Se x ( ) using temperature dependent Bi L3 -edge extended x-ray absorption fine structure measurements. The results reveal that the local structure of the two compounds is significantly different. The BiS2 sub-lattice is largely distorted in LaOBiS2 ( x = 0.0), with two in-plane Bi–S1 distances separated by ̃0.4 Å instead LaOBiSSe ( x = 1.0) showing much smaller local disorder with two in-plane Bi–Se distances in the plane being separated by ̃0.2 Å. Temperature dependent study shows that the two Bi–S1 distances are characterized by different bond strength in LaOBiS2 ( x = 0.0) while it is similar for the Bi–Se distances in LaOBiSSe ( x = 1.0). The out of plane Bi–S2 bond is harder in LaOBiSSe indicating that the structural instability of BiS2 layer has large effect on the out-of-plane atomic correlations. The results suggest that the local structure of LaOBiS2− x Se x is an important factor to describe differing electronic and thermal transport of the two compounds.